Hydrogenation of Pd/Mg films: A quantitative assessment of transport coefficients. (22nd October 2019) - Hadjixenophontos, Efi; Zhang, Kun; Weigel, Andreas; Stender, Patrick; Schmitz, Guido
Abstract: Due to increasing energy demands, interest in hydrogen storage is substantial. Magnesium is one of the most attractive systems, yet, development for practical application remains challenging. By combination of X-ray diffraction, electron microscopy and in-situ measurements of resistivity we determine the diffusion coefficient of hydrogen in MgH2 at technically relevant pressure (20 bar). Pd coated thin films of well-defined thickness enable a quantitative evaluation of the hydrogenation rate. From this, we detect linear to parabolic kinetic transition and obtain the diffusion coefficient of hydrogen in MgH2 . Measurements at different temperatures (RT-300 °C) demonstrate an Arrhenius behaviour with an activation energy E a = 28.1 kJ mol −1 . This low value and the transformation into a nanocrystalline microstructure upon hydrogenation indicate grain boundary diffusion as the essential mechanism. In completion, the interface Pd/Mg is studied. Mg5 Pd2 and Mg6 Pd form at elevated temperatures required for dehydrogenation. These phases affect, but do not prevent, further hydrogen loading. Graphical abstract: Image 1 Highlights: In-situ measurements of resistivity quantify the kinetics of MgH2 formation in thin films. Linear to parabolic transition in the kinetics of hydride formation is demonstrated. Diffusion coefficients of H in MgH2 at different temperatures demonstrate an Arrhenius behaviour. Low activation energy and nano-crystallinity suggest a grain boundary diffusion mechanism. Intermetallic phases of Mg/Pd affect but do not prevent further hydrogen loading.